Flow and noise predictions of the isolated subsonic jets from the Doak Laboratory experiment - Gryazev, Vasily; Markesteijn, Annabel P.; Karabasov, Sergey A.; Lawrence, Jack; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2022)
Flow and noise solutions using Large Eddy Simulation (LES) are evaluated for two jets at acoustic Mach numbers 0.6 and 0.8. The jets correspond to Doak Laboratory Experiment performed at the University of Southampton. LES method is based on the Compact Accurately Boundary-Adjusting High-Resolution Technique (CABARET) scheme and is implemented on Graphics Processing Units. In comparison with many other jet noise benchmarks, the Doak jet cases include well-defined boundary conditions corresponding to the meanflow velocity and turbulent intensity profiles measured just downstream of the nozzle exit. The far-field noise predictions are obtained using two approaches. First, the LES solutions are coupled with the penetrable surface formation of the Ffowcs Williams–Hawkings method. The second approach is based on the reduced-order implementation of the Generalised Acoustic Analogy model for which time averaged quantities are obtained from the LES solutions. All numerical solutions are compared with the flow and acoustic microphone measurements from the Doak experiment. The results are cross-validated using the sJet code, which corresponds to an empirical model obtained from interpolations over a large set of NASA jet noise data.